Scale Development and Validation for Evaluation of Premium Car Purchases - Ravi, K. R.; Rangarajan, Kalyani (Indian Journal of Marketing, 2016)
This paper investigated the beliefs and evaluations embarked on by a premium car buyer during the process of arriving at a decision to buy a premium car. The authors developed a scale using a sample of premium car buyers across the major cities in India, via two iterations. The first iteration was conducted to identify items that significantly represented beliefs and evaluations of premium car purchases by means of EFA. The second iteration further refined the items using coefficient alpha and confirmatory factor analysis and yielded two constructs. The scale was tested and was found to be reliable and valid in premium car purchases. The scale represented a good initial contribution to understanding premium car purchases and additional investigations are warranted with different samples to establish its reliability and validity.